What’s driving girls’ adolescent marriage decline in Rakai, Uganda? The interplay between adolescent pregnancies and social determinants, 1999 – 2018 - Esther Spindler; Susie Hoffman; Fred Nalugoda; Ivy S Chen; Goleen Samari; Tom Lutalo; Ying Wei; Man Luo; Rebecka Lundgren; John S Santelli (International Journal of Adolescence and Youth)
Few studies have sought to untangle the influence of social determinants and pregnancy on adolescent marriage declines. Using longitudinal data from 15- to 17-year-old girls in the Rakai Community Cohort Survey, we assessed how education, socio-economic status, orphanhood and pregnancy contributed to trends in adolescent marriage. We examined descriptive trends and logistic regressions of the associations between social determinants and adolescent marriage and conducted causal mediation analysis to assess the extent to which pregnancy mediated the effect of education on marriage. Between 1999 and 2018, adolescent marriages and pregnancies dropped substantially (24–6% and 28–8%). Girls’ secondary schooling was strongly associated with lower marriage risk (aOR marriage = 0.09; 95% CI = 0.07–0.12), accounting for time. Lower pregnancy rates partially explained the effect of secondary schooling on lower adolescent marriage (aOR indirect effect = 0.55; 95% CI = 0.421–0.721). Findings affirm the importance of education in preventing adolescent marriages but call attention to the role of pregnancies in influencing adolescent marriages.